PTIP chromatin regulator controls development and activation of B cell subsets to license humoral immunity in mice - Su, Dan (Proc Natl Acad Sci U S A, 2017)
B cell receptor signaling and downstream NF-κB activity are crucial for the maturation and functionality of all major B cell subsets, yet the molecular players in these signaling events are not fully understood. Here we use several genetically modified mouse models to demonstrate that expression of the multifunctional BRCT (BRCA1 C-terminal) domain-containing PTIP (Pax transactivation domain-interacting protein) chromatin regulator is controlled by B cell activation and potentiates steady-state and postimmune antibody production in vivo. By examining the effects of PTIP deficiency in mice at various ages during ontogeny, we demonstrate that PTIP promotes bone marrow B cell development as well as the neonatal establishment and subsequent long-term maintenance of self-reactive B-1 B cells. Furthermore, we find that PTIP is required for B cell receptor- and T:B interaction-induced proliferation, differentiation of follicular B cells during germinal center formation, and normal signaling through the classical NF-κB pathway. Together with the previously identified role for PTIP in promoting sterile transcription at the Igh locus, the present results establish PTIP as a licensing factor for humoral immunity that acts at several junctures of B lineage maturation and effector cell differentiation by controlling B cell activation.